Community Capacity Building in Flood Disaster Mitigation Efforts in Limapuluh Kota Regency - Eri Barlian; Iswandi Umar; Indang Dewata; Yunhendri Danhas; Osronita Osronita; Mira Hasti Hasmira; Linda Handayuni; Aprizon Putra; Serly Mutia Sari (Pascasarjana, Universitas Negeri Padang, 2021)
Disaster mitigation is an effort and or action to reduce disaster risk. Community capacity building in dealing with disasters is an effort to reduce disaster risk. Limapuluh Kota Regency is one of the areas that have a high level of vulnerability to flood disasters. The target of this activity is to increase community capacity in dealing with flood disasters. The efforts made can be divided into five forms, namely 1) strengthening disaster management institutions; 2) early warning of disaster risk; 3) disaster education; 4) reducing risk factors; and 4) development of preparedness in all lines. In the first year, there will be institutional formation and a study of disaster-prone zoning. In the second year, prepare a model for disaster education and study efforts to reduce disaster risk factors. In the third year building preparedness on all lines in the face of disasters. This activity has the output of national and international scientific publications in modeling community capacity building in dealing with flood disasters.